TRAGEDI TALANGSARI: PELANGGARAN HAM YANG MENINGGALKAN LUKA DI LAMPUNG TIMUR TAHUN 1989-2022 - Anisa Fadila dilla; Dewi Retnofirnanda (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2023)
The title of this research is "Talangsari Tragedy: Human Rights Violations That Left Wounds in East Lampung in 1989-2022"February 1989 in Talangsari III Hamlet, Rajabasa Lama Village, Way Jepara District, East Lampung Regency. The Talangsari incident in Lampung became a tragic story that was forgotten by the state. Hundreds of people who were victims at that time seemed to have no right to know what really happened, and to get justice through punishing the perpetrators and restoring their rights. Over the years, the victims who are still suffering from the incident have also experienced terror and intimidation. The method used in this writing is using the historical method. The purpose of this writing is to know the chronology of the Talangsari tragedy, to know the government in overcoming the Talangsari tragedy and the impact of the Talangsari tragedy. The conclusion of this paper is the Talangsari incident for many years, victims who are still suffering from the incident also experienced terror and intimidation from the parties involved in the crime Keywords: Talangsari, Lampung, Tragedy